Rezension von: Simon, Hans, Das Herz unserer Städte Bd. 1, 2, 3, 4 - Brückner, Wilfried (Württembergisch Franken, 1979)
Hans Simon: „Das Herz unserer Städte”. Essen, Richard Bacht. Bd. 1, 1963, 91 S., Bd. 2,1965, 160 S., Bd. 3, 1967, 82 S., Bd. 4,1975, 92 S.